Inpatient palliative care utilization for patients with brain metastases. Issue 4 (24th February 2021) - Price, Meghan; Howell, Elizabeth P; Dalton, Tara; Ramirez, Luis; Howell, Claire; Williamson, Theresa; Fecci, Peter E; Anders, Carey K; Check, Devon K; Kamal, Arif H; Goodwin, C Rory
Abstract: Introduction: Given the high symptom burden and complex clinical decision making associated with a diagnosis of brain metastases (BM), specialty palliative care (PC) can meaningfully improve patient quality of life. However, no prior study has formally evaluated patient-specific factors associated with PC consultation among BM patients. Methods: We examined the rates of PC consults in a cohort of 1303 patients with BM admitted to three tertiary medical centers from October 2015 to December 2018. Patient demographics, surgical status, 30-day readmission, and death data were collected via retrospective chart review. PC utilization was assessed by identifying encounters for which an inpatient consult to PC was placed. Statistical analyses were performed to compare characteristics and outcomes between patients who did and did not receive PC consults. Results: We analyzed 1303 patients admitted to the hospital with BM. The average overall rate of inpatient PC consultation was 19.6%. Rates of PC utilization differed significantly by patient race (17.5% in White/Caucasian vs 26.0% in Black/African American patients, P = .0014). Patients who received surgery during their admission had significantly lower rates of PC consultation (3.9% vs 22.4%, P < .0001). Patients who either died during their admission or were discharged to hospice had significantly higher rates of PC than those who were discharged home or to rehabilitation ( P < .0001). Conclusions: In our dataset, PC consultation rates varied by patient demographic, surgical status, discharging service, and practice setting. Further work is needed to identify the specific barriers to optimally utilizing specialty PC in this population.